Comprehensive pan-cancer analysis of CD73: Explore its association with prognosis and tumor immune microenvironment - Chen Chen; Sasa Liu; Yanfen Ma (Heliyon)
Background: CD73 is adenosine generation molecule, which is involved in the immune regulation. However, the roles of CD73 in the tumor microenvironment remain unknown. Methods: CD73 expression levels in pan-cancers were analyzed, based on The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) and Human Protein ALTAS (HPA) databases. Kaplan-Meier (KM) plotter was used to analyze the prognostic values of CD73. Immune scores in pan-cancers was evaluated by ESTIMATE. TIMER2.0 and UCSCXena were used to explore the correlation between CD73 and immune infiltration/immune checkpoints/tumor mutation burden (TMB)/microsatellite instability (MSI). CD73 expression correlated genes in tumor tissues were screened by using LinkedOmics tool. Results: Firstly, CD73 was significant increased in following cancer types: esophageal carcinoma (ESCA), glioblastoma multiforme (GBM), head and neck squamous cell carcinoma (HNSC), brain lower grade glioma (LGG), lung adenocarcinoma (LUAD), pancreatic adenocarcinoma (PAAD) and stomach adenocarcinoma (STAD). Secondly, high CD73 expression was associated with poor overall survival in patients with breast invasive carcinoma (BRCA), CESC, HNSC, liver hepatocellular carcinoma (LIHC), LUAD, lung squamous cell carcinoma (LUSC), PAAD and STAD. However, in KIRC and UCEC, patients high CD73 expression showed a favorable prognosis. Thirdly, the immune scores of the high CD73 expression in bladder urothelial carcinoma (BLCA), BRCA, kidney chromophobe (KICH), LUAD, LUSC, ovarian serous cystadenocarcinoma (OV), pheochromocytoma and paraganglioma (PCPG), prostate adenocarcinoma (PRAD), and skin cutaneous melanoma (SKCM) were significant higher than that of patients with low CD73 expression. Furthermore, we observed a positive correlation between CD73 and the multiple immune cells infiltration, including CD4+ memory T cells, CD8+ T cells, Treg cells, myeloid DC and macrophage, particularly in BRCA and LUAD. There was no strong correlation between CD73 and TMB/MSI. In LUAD, CD73 expression correlated genes were mainly enrichment in positive regulation of cell proliferation, cell adhesion, positive regulation of kinase activity, cellular response to LPS. However, in UCEC, CD73 correlated genes were mainly associated with fatty acid omega-oxidation, protein localization to endoplasmic reticulum exit site, endoplasmic reticulum to Golgi vesicle-mediated transport. Conclusion: CD73 could be used to predict the prognosis of patients with several cancers. The potential functional mechanism of CD73 involved in cancer progress may not only dependent on its immunomodulatory effects.